PERAN TEKNOLOGI INFORMASI PADA PARIWISATA INDONESIA - Jack Febrian Rusdi (Universitas Ma'soem, 2019)
Information and Communication Technology (IT) is a part that is firmly attached to the progress of world tourism. Unfortunately, this research on the role of IT has not received much attention from various studies produced in Indonesia. This article discusses the part of IT that can implement in multiple aspects of tourism. The method used is a literature review sourced from the Garuda portal. The study provides various research areas that can be carried out within the tourism sector, specifically to support the growth of tourism research and information technology in Indonesia.